Clinico-hematological evaluation in cases of pancytopenia at tertiary care centre: largest cross-sectional study - Munde, Haridas S.; Shende, Nitin Y.; Nagare, Swati D. (International Journal of Research in Medical Sciences, 2021)
Background: Pancytopenia is characterised by a reduction in all the three cellular elements of blood (erythrocytes, leukocytes and platelets) below the normal reference range leading to anaemia, leucopenia and thrombocytopenia. It is a feature of many serious conditions. The present study was conducted to assess aetiology, clinical profile and bone marrow morphology of conditions presenting with pancytopenia. Methods: A two years cross-sectional study from July 2017 to June 2019 was conducted in the Department of Pathology. Total of 300 pancytopenia patient were studied and their clinical features, peripheral smear finding and bone marrow morphology were studied by using marrow aspiration and biopsy. Results: Among 300 cases studied, maximum patients were in the age group 11-20 years (19.66%) with male (50.66%) predominance. Most of the patients presented with weakness (91.66%) and fever (56.66%) as chief complains. The commonest physical finding was pallor (94%) followed by splenomegaly (27.33%). Macrocytic anaemia (43.66%) was commonest peripheral finding. The commonest cause of pancytopenia was megaloblastic anaemia (32.66%) followed by dimorphic anaemia (21%), aplastic anaemia (16%) and acute leukaemia (13.33%). Conclusions: The present study concludes that detailed clinical history, primary haematological investigations along with bone marrow examinations is essential to determine the cause of pancytopenia.